Market Reaction of the Indonesian Banking Sector to the Announcement of MSCI Index Rebalancing Suspension - Muhammad Wildan Purnama; Nur Kholidah (International Journal of Business, Management and Economics, 2026)
This study looks into how Indonesian banking stocks reacted to the January 28, 2026, announcement that the MSCI Index rebalancing would be suspended. Using a 15-day observation window that included 7 trading days prior to and 7 trading days following the announcement, an event research methodology was employed. Purposive sampling was used to select the 15 banking companies listed on the IDX. "Average Abnormal Return" (AAR) and "Average Trading Volume Activity"(ATVA) were used to gauge the market's response. The empirical results reveal no statistically significant differences in either AAR or ATVA surrounding the announcement period. These findings indicate that investors did not view the suspension of MSCI Index rebalancing as sufficiently relevant to influence investment decisions in the Indonesian banking sector